The Effect of Exercises and Therapeutic Means in Rehabilitating Deltoid Partial Rupture and Restricted Shoulder Joint Movement in Some Advance Basketball Players - Ahmed, Elaf; Mohammed , Ahmed (Journal of Physical Education, 2019)
The importance of the research lies in using rehabilitating exercises in sport injuries therapy. The problem of the research lies in the lack of interest in therapeutic exercises in treating injured players in general and in basketball players with deltoid rapture in particular as well as the wide spread of uncontrolled medicine. The researchers used the experimental method on (6) advance basketball players. the data was collected and treated using proper statistical operations to conclude that therapeutic exercises and means have a positive effect in rehabilitating deltoid rapture in basketball players. Finally the researcher recommended using these therapeutic exercises in rehabilitating other injuries in other sports. In addition to that, they recommended holding courses for developing rehabilitation skills.